ANALISIS PENGARUH IMPLEMENTASI SISTEM KESELAMATAN KESEHATAN KERJA (K3) TERHADAP UNSAFE ACTION DI PT EGS INDONESIA - Rici Riyansyah (Universitas Pahlawan, 2021)
Work accident occur because of two groups. The first group is mechanical and environmental factors (unsafe conditions). The second group is the human factor (unsafe action). Human resources are very important assets in a company or organization, where employees can become potentials if managed properly and properly. On the contrary, it can become a burden if you are mismanaged. One of the efforts that companies can make to maintain employee health and safety is to implement employee health and safety management by implementing a good and correct application of an occupational safety and health management system (SMK3). Unsafe acts at PT EGS Indonesia. This type of research is descriptive quantitative with the approach used is cross sectional. The data analysis technique used in this research is SEM (Structural Equation Model). The results showed that the OSH management system in the form of leadership and policy had a negative effect on unsafe action. The OSH Management system in the form of planning has a negative effect on unsafe actions. The OSH management system in the form of its implementation has a negative effect on unsafe actions. The OSH Management system in the form of performance evaluation has a negative effect on unsafe actions. The OSH management system in the form of corrective action has a negative effect on unsafe actions. The conclusion is that the overall occupational health safety management system in the form of leadership and policies, planning, implementation, performance evaluation and corrective action has a negative effect on unsafe action.